The Influence of leadership example, rewards, and punishments on the development of MSMEs - Setiawan, Muchammad Firman; Andriani, Dewi (Institute of Computer Science (IOCS), 2024)
The development of the business world today has given rise to various challenges and competition that must be faced by MSMEs. MSMEs need contributions from their employees, who can play an active role so that the MSME company can survive and be able to compete. For this reason, employees are required to always be disciplined in complying with company regulations and policies so that the company continues to exist and develop. This research aims to determine the influence of leadership example, remuneration and punitive sanctions on the development of MSMEs. The respondents in this research were 30 employees of Pia RB MSMEs in PIA Waru village, Gempol District, Pasuruan, using multiple linear regression. From the anova test or F test, it was obtained that the calculated F was 3,528 with a significance value of 0.029 <0.05, which means that leadership example, remuneration and punitive sanctions simultaneously have a significant influence on the development of MSMEs. The results of the analysis on the remuneration variable obtained the highest t count, namely 2.627 and the significance value was 0.014, which was the most significant compared to the other variables. So the remuneration variable is stated as the variable that has the most dominant influence on the MSME development variable